Librarians and Repository Data - Yupi Royani; Rochani Nani Rahayu; Ahmad Saefudin Suriapermana (Program Studi Ilmu Perpustakaan UIN Alauddin, 2020)
This study aims to determine the librarian's understanding of data repository which include benefits, engagement of librarians in repository management, and repository implementation. The study has surveyed librarians at the Indonesian Institute of Sciences located in Jakarta, Bogor, Cibinong, and Serpong by distributing 45 questionnaires, but only 36 returned. The data were tabulated and analyzed using graphs/diagrams. The respondents of the study were female (61.1%) and male (38.9%). The education background of the respondents was undergraduate (50%), the most working period is between 20-30 years (38.9%), and the most work locations were in Jakarta (70.6%). The study showed that respondents with an undergraduate background and those who work in Jakarta have the highest understanding of the repository (69%). The most involved in repository management were those with bachelor's degrees and working in Jakarta (52%). Respondents who were involved in the socialization of the data repository were 47%, and those who were not involved were 44%. As many as 44% of respondents stated that the data repository has been implemented, and the remaining 56% said it has not been implemented. In conclusion, most respondents understand the data repository, especially those with a bachelor's degree, and were working in Jakarta. The data repository has not been implemented properly due to lack of outreach to researchers and their low trust in the data repository.